PROFIL PENAMBANG EMAS DI KECAMATAN BEUTONG KABUPATEN NAGAN RAYA - Fitra Ramadi; Sofyan Syahnur (Fakultas Ekonomi dan Bisnis UNSYIAH, 2019)
AbstractThis study aims to determine the profile of gold miners in Beutong District, Nagan Raya District. The data used are Primary data obtained from observations and direct interviews. The sample used amounted to 75 people who work as miners and who live around the mining area. The data collection model is done by interview technique. The analysis used was qualitative descriptive. Based on the results of the study, it was found that the profile of gold producers in Beutong Subdistrict, Nagan Raya Regency was dominated by male workers, and from the education status of miners had an education status from non-school to undergraduate. The average education status of miners is high school graduates. Then the previous employment status of mining workers mostly worked as farmers and entrepreneurs. The results of this study are expected by the existence of mining activities in Beutong District can increase revenue and also from the other side the government is expected to make rules so that mining activities become environmentally friendly. Keywords: Profile, Gold Miner, Beutong District.